The Influence Differences of Tabata Training and Circuit Training on Increasing Endurance in Obesity - Ayu Pratiwi, Nilawati; Dika Rizki Imania; Muhammad Irfan (Jurnal Kesehatan Cendikia Jenius, 2025)
Background : Obesity can reduce a person’s immune system due to various factors affecting overall helath. Therefore, it is essential to maintain body weight and adopt a healthy lifestyle to increase endurance. Aim of study : The study aimed to determine the difference in the effect of Tabata Training and circuit trainig on increasing endurance in obesity. Research Method : The study applied quasi-experimental with a research design using a pre-test and post-test two-group design, a sample size of 24 people. Then divided into two groups. Group I Tabata training, and group II circuit training. This research was carried out for 4 weeks, with 3 training sessions per week by students of the Bachelor of Nursing study program at Aisyiyah University, Yogyakarta. Data collection was used as a questionnaire regarding obesity and measuring increased endurance using the Multistage Test after and before treatment. Findings : Testing hypothesis I using a Paired Sample T-test obtained value of p0<000 (<0.005), and the results of testig hypothesis II using a Paired Sample T-test obtained a value of p0<000 (<0.005), which means that both treatments have the effect of increasing Endurance on Obesity. The results of hypothesis III using the Independent Sample T-test obtained a p-value <0.001 (>0.005), which means there is a difference between the two exercises. Conclusion : There is difference in the effect of Tabata training and circuit training on increasing endurance in obesity. Suggestion : This research can become material for study an information for further research.